EVALUATION OF CALCULATING THE COST OF THE PRODUCT THROUGH THE ENTRANCE TO ACCOUNTING FOR ACCOMPLISHMENT APPLIED RESEARCH IN ELECTRICAL METROLOGY LAB - Lect . Dr . Khalil Ibrahim Ismail (Scholar Express Journals, 2022)
The research seeks to shed light on calculating product cost in the light of the modern business environment that witness continuous and rapid development through the development of production . Whether it is a commodity or a service for the purpose of achieving the requirements , desires of customers at the lowest cost and the best quality by meeting the requirements of the customer. Therefore the economic units look for ways to work to evaluate the calculation of product costs and work to economize costs by using accounting on accomplishment to develop the reality of costs accounting and to measure costs clearly and fair manner that has a positive impact on managing economic units through rationalizing administrative decisions and the ability to face developments are occurred at the level of the labor market and the desires of the customer . While the research sample is the electrical gauges factory . Whereas the period is in year 2017 , to calculate the cost of the product. The research has reached the most important conclusions to work on developing the cost systems are applied in the Iraqi industrial companies, including Diyala State Company for Electrical Industries, the metrology laboratory by using modern advanced methods for its ability to provide information . Whether financial or non-financial to the aid administration to help in planning and decision making
Keywords: Electrical Industries; metrology laboratory